Development of ROS-Modulating Nanoparticles for Anti-Inflammatory Therapies - Courtemanche, Amandine (Université d'Ottawa / University of Ottawa, 2025)
Inflammation is a normal protective biological response mediated by a variety of pathways, many of which involve reactive oxygen species (ROS). ROS contribute to the progression of inflammation either by their involvement in inflammatory signaling, or via the oxidative stress they produce when present in elevated levels. As a prospective therapy for ROS and inflammation reduction, a novel ROS-sensitive and ROS-scavenging nanoparticle (NP) system was developed in this project. To this end, a library of biomaterials was synthesized, characterized, and assessed for their potential in forming ROS-sensitive boronic ester bonds. NP systems were assembled using these synthesized polymers and 1 of 3 ROS-scavengers: tannic acid (TA), gallic acid (GA) and epigallocatechin gallate (EG). The NPs demonstrated ROS-dependent properties in solution and in vitro. Additionally, they exhibited good cellular uptake and low cytotoxicity. Thus, we have obtained an optimized system which successfully activates in high ROS conditions, reduces ROS levels in inflammatory conditions, and exhibits potential for inflammation reduction.
Keywords: ROS; Reactive oxygen species; Nanoparticles; Inflammation; Anti-inflammatory therapies